Pentachlorophenol alters the acetate-assimilating microbial community and redox cycling in anoxic soils. (April 2019) - Xu, Yan; He, Yan; Egidi, Eleonora; Franks, Ashley E.; Tang, Caixian; Xu, Jianming
Abstract: Acetate is a common electron donor that can drive microbial reductive processes in anaerobic environments. Apart from acting as a terminal electron acceptor, chlorinated organic pollutant of pentachlorophenol (PCP) has antimicrobial properties but little is known about its effect on anaerobic microbial populations during bioremediation. To elucidate the effect of PCP on the anaerobic microbial community, DNA-based stable isotope probing was performed using 13 C-acetate as a substrate in two depths (0–20 cm and 80–100 cm) of mangrove soils. The addition of PCP had little influence on Fe(III) reduction, but dramatically inhibited the SO4 2− reduction, resulting in a high emission of CH4 under anoxic conditions. Correspondingly, PCP significantly affected the composition of prokaryotic 13 C-labeled OTUs (Operational Taxonomic Units) at both soil depths. Members of Clostridiales (Firmicutes) and Burkholderiales (Betaproteobacteria) were dominant 13 C-acetate utilizers and potential PCP degraders. The PCP addition decreased sulfate reduction process through inhibition of classical sulfate- and sulfur-reducing bacteria belonging to families of Desulfarculaceae, Desulfobulbaceae and Desulfobacteraceae. Our study showed that indigenous microbial communities associated with terminal electron-accepting pathways (e.g. Fe 3+ and SO4 2− reduction) changed differently during PCP dechlorination. These findings suggest a great impact of chlorinated pollutants on the soil biogeochemical processes. Graphical abstract: Image 1 Highlights: This study used 13 C-acetate as a substrate for bacterial anaerobic respiration. Pentachlorophenol (PCP) inhibited SO4 2− reduction but facilitated CH4 emission. Clostridiales and Burkholderiales were dominant acetate-utilizers during PCP degradation. PCP inhibited the growth of Desulfarculaceae, Desulfobulbaceae and Desulfobacteraceae.